Експериментальне обґрунтування розвитку спеціальної витривалості спортсменів юнаків в процесі занять вільною боротьбою - Лаврентьєв, Олександр Миколайович; Малинський, Ігор Йосипович; Махнюк, Володимир Володимирович (Український державний університет імені Михайла Драгоманова, 2026)
У статті розглядаються аспекти, щодо розвитку та вдосконалення навчально-тренувального процесу спортсменів - юнаків в процесі занять вільною боротьбою. Основними компонентами є засоби організації та проведення тренувальних занять із загальної та спеціальної фізичної підготовки, а також формування навантажень і використання технічних елементів та вправ для вдосконалення спеціальної витривалості. Планування тренувального процесу у вільній боротьбі є ключовим елементом управління рівнем підготовленості спортсменів. Воно передбачає завчасне визначення умов, методів, засобів і форм реалізації завдань спортивної підготовки, а також прогнозування результатів, які індивідуально ставляться перед кожним борцем. У всіх видах боротьби крім змагальної складової для прогресу обов’язково потрібно використовуються допоміжні вправи (загально-розвиваючі, допоміжні та спеціально-розвиваючі), що допоможуть в організації тренувальних навантажень за періодами підготовки та зберегти довготривалий виступ спортсменів на змаганнях. Дослідження проводилось під час переддипломної практики на базі спортивного клубу «Бойова жаба» у теоретичному дослідженні прийняло участь (n=25) респондентів, а у практичній складовій дослідженні взяли участь юні спортсмени віком 12-15 років (n= 16) чол.

The article considers aspects of the development and improvement of the educational and training process of young athletes in the process of freestyle wrestling. The main components are the means of organizing and conducting training sessions in general and special physical training, as well as the formation of loads and the use of technical elements and exercises to improve special endurance. Planning the training process in freestyle wrestling is a key element of managing the level of preparedness of athletes. It involves the early determination of conditions, methods, means and forms of implementing sports training tasks, as well as forecasting the results that are individually set for each wrestler. In all types of wrestling, in addition to the competitive component, for progress, it is necessary to use auxiliary exercises (general, auxiliary and special-development), which will help in organizing training loads for training periods and maintain the long-term performance of athletes at competitions. That is, for the development of special endurance of young wrestlers, it is advisable to use circuit training, a game method and a competitive method, which, according to the specifics of physical activity, include special motor actions with appropriate practice, often in conditions that simulate wrestling matches. Exercises with additional weights or overcoming resistance are used, as well as motor games that require endurance, but with the possibility of regulating intensity, etc. The study was conducted during pre-diploma practice from September 29 to November 21, 2025 on the basis of the sports club "Fighting Frog". (n = 25) respondents participated in the theoretical study, and young athletes aged 12-15 years (n = 16) people participated in the practical component of the study.
Experimental substitution of the development of special endurance in young athletes in the process of freestyle wrestling
Keywords: спеціальна витривалість; вільна боротьба; єдиноборства; фізичні якості; планування; тренування; special endurance; freestyle wrestling; martial arts; physical qualities; planning; training